Role of diagnostic laparoscopy in chronic abdominal pain - Dnyanmote, Anuradha; Srivastava, Neha; Gope, Debabrata; Tyagi, Ashish (International Surgery Journal, 2020)
Background: Chronic idiopathic pain syndromes are amongst the most challenging and demanding conditions to treat across the whole age spectrum. Despite these patients having undergone numerous diagnostic work-ups, their pain remains a challenge to all known diagnostic and treatment methods. Methods: To evaluate role of diagnostic laparoscopy in chronic abdominal pain a prospective observational study was done. The present study was conducted on patients with undiagnosed chronic abdominal pain coming to the Department of Surgery, Dr. D. Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune. 75 patients with chronic abdominal pain who attend the General Surgery Department (OPD) were included in the study. Patients were included in the study after taking their voluntary informed consent. The categorical variables were assessed using Pearson chi-square. The quantitative variables were assessed using T-test. The test was considered significant only if the p value comes out to be less than 0.05. Results: Based on the findings of the study after performing diagnostic laparoscopy for 75 patients with chronic abdominal pain it was found that most common finding was of appendicitis (32%) followed by abdominal Koch’s (24%) and post-operative pain relief using VAS showed p value of less than 0.05 at 3 months of follow up post diagnostic laparoscopy. Conclusions: The present study concluded that laparoscopy is an effective diagnostic role in evaluating patients with chronic abdominal pain, in whom conventional methods of investigations have failed to elicit a certain cause. The advantage of diagnostic laparoscopy over non-invasive methods is the ability to perform therapeutic procedure at the same time in cases of chronic abdominal pain. Diagnostic laparoscopy is safe, cosmetically better and having less morbidity.